1973
DOI: 10.1038/bjc.1973.163
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoassay of Tumour Specific Transplantation Antigen of a Chemically Induced Rat Sarcoma: Circulating Soluble Tumour Antigen in Tumour Bearers

Abstract: Summary.-The tumour specific transplantation antigen (TSTA) from a chemically induced rat sarcoma has been isolated as an electrophoretically homogeneous soluble material by affinity chromatography using a Sepharose bound antibody raised to the tumour in syngeneic rats. The TSTA is specific for the particular tumour used (the MC-1 sarcoma) and does not cross-react with material extracted from other rat sarcomata. In addition, a material with different physicochemical properties which cross-reacted with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1975
1975
1980
1980

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Loss of LA1 reactivity in melanoma after tumor excision was also observed by Marti and T h o m~o n .~~ Vol. 39 Rapid disappearance of measurable antitumor immunity was reported by Unsgaarde and O'Toole and O'Toole, et al with the microcytotoxicity assays in melanoma and bladder cancers. 2841 Moreover, in the leukocyte migration test in breast cancer, Jones, et aLZ0 and Rieche, et al" reported that reactivity rapidly disappeared after the removal of the primary tumor.…”
mentioning
confidence: 84%
“…Loss of LA1 reactivity in melanoma after tumor excision was also observed by Marti and T h o m~o n .~~ Vol. 39 Rapid disappearance of measurable antitumor immunity was reported by Unsgaarde and O'Toole and O'Toole, et al with the microcytotoxicity assays in melanoma and bladder cancers. 2841 Moreover, in the leukocyte migration test in breast cancer, Jones, et aLZ0 and Rieche, et al" reported that reactivity rapidly disappeared after the removal of the primary tumor.…”
mentioning
confidence: 84%
“…Macrophages from immune mice can be rendered non-specifically cytotoxic on the addition of antigen, and normal macrophages may become cytotoxic on binding immune complexes on their surface (Evans and Alexander, 1976). A growing sarcoma, causing a continuous presence of circulating antigen or antigen-antibody complexes (Thomson et al, 1973) …”
Section: I)scussionmentioning
confidence: 99%
“…At the present time the major problem limiting progress in this area is the lack of sensitive and quantitative immunoassays for soluble tumour-specific antigens. However, the early work of Thomson et al (1973) using a solid-phase radioimmunoassay for antigen in the serum of rats bearing grafts of a 3-methylcholanthrene-induced sarcoma suggests that it is possible to develop cellfree immunoassays of the required sensitivity, though in more recent studies Thomson et al (1976) have returned to indirect membrane-immunofluoresence tests to monitor the purification of sarcoma-associated antigens.…”
Section: Discussionmentioning
confidence: 99%